The Reverse Chameleon Effect: Negative Social Consequences of Anatomical Mimicry - Casasanto, Daniel; Casasanto, Laura Staum; Gijssels, Tom; Hagoort, Peter (Frontiers in Psychology, 2020)
Bodily mimicry often makes the mimickee have more positive feelings about the mimicker. Yet, little is known about the causes of mimicry’s social consequences. When people mimic each other’s bodily movements face to face, they can either adopt a mirrorwise perspective (moving in the same absolute direction) or an anatomical perspective (moving in the same direction relative to their own bodies). Mirrorwise mimicry maximizes visuo-spatial similarity between the mimicker and mimickee, whereas anatomical mimicry maximizes the similarity in the states of their motor systems. To compare the social consequences of visuo-spatial and motoric similarity, we asked participants to converse with an embodied virtual agent (VIRTUO), who mimicked their head movements either mirrorwise, anatomically, or not at all. Compared to participants who were not mimicked, those who were mimicked mirrorwise tended to rate VIRTUO more positively, but those who were mimicked anatomically rated him more negatively. During face-to-face conversation, mirrorwise and anatomical mimicry have opposite social consequences. Results suggest that visuo-spatial similarity between mimicker and mimickee, not similarity in motor system activity, gives rise to the positive social effects of bodily mimicry.